ABHD5 inhibits YAP-induced c-Met overexpression and colon cancer cell stemness via suppressing YAP methylation - Yan Gu; Yanrong Chen; Lai Wei; Shuang Wu; Kaicheng Shen; Chengxiang Liu; Yan Dong; Yang Zhao; Yue Zhang; Chi Zhang; Wenling Zheng; Jiangyi He; et al. (Nature Communications, 2021)
This study reveals an unrecognized role of ABHD5 in regulating colon cancer stemness via controlling YAP methylation and nuclear localization, further explaining the molecular mechanism through which ABHD5 functions as a tumour suppressor gene in colon cancer.